PROMOTING LESSON STUDY AT ENGLISH FOR SPECIFIC PURPOSES (ESP): TEACHER’S BEST PRACTICE CONTEXT - Masyhud Masyhud (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2018)
English for Specific Purposes (ESP) is an exciting movement in language education.  It widens the opportunities for English teachers and researchers to explore the curriculum, course planning and implementation of ESP education. However, there are several problems in teaching ESP. one of the most problems is students’ engagement in the class because they felt learning English unrelated to their major. Therefore, this research concerns to investigate the implementation of Lesson Study in Teaching English for Specific Purposes (ESP) to sharpen the students’ critical thinking. Lesson Study has been a precious motion for recent decades, principally for the sake of teachers’ professional development and students’ critical thinking. This research involved 5 ESP teachers. They acquired equal chance to be a teacher model and observer in the LS process. This research conducted in 2 cycles with three phases; Plan, Do, and See. This research employed observation and document analysis as the tools to collect the data. This Lesson study was implemented into two stages, planning and implementation. However, it can encourage the students to participate actively along the learning process because cycle 1 can provide student’s participation 90% and in cycle 2, 95% of students involved in the learning process.